Anatomic Thoracoscopic Repair of Esophageal Atresia - Fonte, Joana; Barroso, Catarina; Lamas-Pinheiro, Ruben; Silva, Ana R.; Correia-Pinto, Jorge (Frontiers in Pediatrics, 2017)
Background: The thoracoscopic approach to repair esophageal atresia (EA) with tracheoesophageal fistula (TEF) provides excellent view, allowing the most skillful surgeons to spare the azygos vein by performing the esophageal anastomosis over (on the right side) the azygos vein. Seeking the most anatomic repair, we started to perform the esophageal anastomosis underneath (on the left side) the azygos vein: Anatomic Thoracoscopic Repair of Esophageal Atresia (ATREA). We aim to compare results of ATREA with the classic thoracoscopic repair. Methods: During last 4 years, in our center, all infants with EA with distal TEF were operated by thoracoscopy sparing the azygos vein. According to the surgical technique two groups were created: Group A - treated with ATREA and Group B - treated with classic thoracoscopic repair over (on the right side) the azygos vein. We retrospectively collected data regarding features of the newborn (gestational age, gender, karyotype changes, associated anomalies, birth weight), surgery (operative technique, operative time and surgical complications), hospitalization (duration of mechanical ventilation, thoracic drainage, time for the first feeding, time of admission and early complications) and follow-up (tracheomalacia, gastroesophageal reflux disease, anastomotic stricture, recurrence of fistula). Results: Group A had 7 newborns and Group B had 4 newborns. There were no statistically significant differences between both groups concerning the evaluated variables on surgery, hospitalization and follow-up. Nevertheless, in group A there was an infant with a right aortic arch where ATREA was particularly useful as it avoided that the azygos vein and the aortic arch were left compressed in between the esophagus and trachea. Postoperatively one patient of Group B had a major anastomotic leak with empyema requiring surgical re-intervention. During follow-up, anastomotic stricture requiring esophageal dilation occurred with similar rates in both groups. In Group B one patient had severe and symptomatic tracheomalacia requiring aortopexy and severe gastroesophageal reflux disease requiring fundoplication. No patients developed recurrent fistula. Conclusions: The ATREA is feasible in the great majority of patients with EA with TEF without compromising long-term results and might be particularly useful for those infants with malformations of the cardiac venous return vessels and/or major aortic malformations.